High-fat diet alters weight, caloric intake, and haloperidol sensitivity in the context of effort-based responding. Issue 5 (August 2017) - Robertson, Stephen H.; Boomhower, Steven R.; Rasmussen, Erin B.
Abstract : High-fat (HF) diets result in weight gain, hyperphagia, and reduced dopamine D2 signaling; however, these findings have been obtained only under free-feeding conditions. This study tested the extent to which HF diet affects effort-dependent food procurement and the extent to which dopamine signaling is involved. Male Sprague-Dawley rats consumed either a HF ( n =20) or a standard-chow ( n =20) diet. We assessed the sensitivity to effort-based reinforcement in 10 rats from each group by measuring consumption across a series of fixed-ratio schedules (FR 5–FR 300) under a closed economy and quantified performance using the exponential-demand equation. For each FR, acute injections of 0 or 0.1 mg/kg of haloperidol, a D2 antagonist, were administered to assess dopamine-related changes in consumption. Rats fed a HF diet consumed more calories and weighed significantly more than rats fed standard-chow. Food consumption decreased in both groups in an effort-dependent manner, but there were no group differences. Haloperidol reduced responding in an FR-dependent manner for both groups. Animals exposed to a HF diet showed an altered sensitivity to haloperidol relative to rats fed a standard diet, suggesting that HF diet alters sensitivity to DA signaling underlying effort-based food procurement.